1987
DOI: 10.1083/jcb.104.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Identification and purification of a sperm surface protein with a potential role in sperm-egg membrane fusion.

Abstract: Abstract. Sperm-egg plasma membrane fusion during fertilization was studied using guinea pig gametes and mAbs to sperm surface antigens. The rnAb, PH-30, strongly inhibited sperm-egg fusion in a concentration-dependent fashion. When zona-free eggs were inseminated with acrosome-reacted sperm preincubated in saturating (140 lxg/ml) PH-30 mAb, the percent of eggs showing fusion was reduced 75 %. The average number of sperm fused per egg was also reduced by 75 %. In contrast a control mAb, PH-I, preincubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
207
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(213 citation statements)
references
References 31 publications
2
207
2
1
Order By: Relevance
“…In viral infections such as influenza virus (Anders et al 1990) or HIV (Lifson et al 1986, Matthews et al 1987 infection, the involvement of terminal highmannose type oligosaccharide has been reported. Cell-cell fusion reactions such as sperm-egg fusion (Primakoff et al 1987, Blobel et al 1990, myoblast fusion (Kaufman et al 1985, Rosenberg et al 1985, Menko & Boettiger 1987, Rosen et al 1992, monocyte fusion (Most et al 1990), or preosteoclast fusion (Kurachi et al 1993) are also protein mediated. From these observations (Kurachi et al 1994), we have already reported that mannose residues are expressed on the outer membranes of monocytes during osteoclast differentiation using pradimicin derivatives, which are antiviral and antifungal both in vitro and in vivo, and recognize and bind specific sugars such as mannose residues (Oki et al 1988(Oki et al , 1990.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In viral infections such as influenza virus (Anders et al 1990) or HIV (Lifson et al 1986, Matthews et al 1987 infection, the involvement of terminal highmannose type oligosaccharide has been reported. Cell-cell fusion reactions such as sperm-egg fusion (Primakoff et al 1987, Blobel et al 1990, myoblast fusion (Kaufman et al 1985, Rosenberg et al 1985, Menko & Boettiger 1987, Rosen et al 1992, monocyte fusion (Most et al 1990), or preosteoclast fusion (Kurachi et al 1993) are also protein mediated. From these observations (Kurachi et al 1994), we have already reported that mannose residues are expressed on the outer membranes of monocytes during osteoclast differentiation using pradimicin derivatives, which are antiviral and antifungal both in vitro and in vivo, and recognize and bind specific sugars such as mannose residues (Oki et al 1988(Oki et al , 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal high-mannose type oligosaccharide on the cell surface mediates cell-cell fusion reactions such as sperm-egg fusion (Primakoff et al 1987, Blobel et al 1990 and myoblast fusion (Kaufman et al 1985, Rosenberg et al 1985, Menko & Boettiger 1987, Rosen et al 1992. The involvement of terminal high-mannose type oligosaccharide has also been reported in the events of viral infections such as the influenza virus (Anders et al 1990) or human immunodeficiency virus (HIV) (Lifson et al 1986, Matthews et al 1987.…”
Section: Introductionmentioning
confidence: 99%
“…The designation disintegrin refers to its property of disrupting integrin binding to classic ligands, including fibronectin and laminin. The ␣ and ␤ subunits of the heterodimeric sperm protein fertilin (also designated ADAM-1 and ADAM-2, respectively; see http:// www.people.Virginia.edu/ϳjw7g/ Table_of_the_ADAMs.html for a table of ADAM gene and protein nomenclature) were the first members of the ADAM family to be recognized as spermatogenic cell-specific and implicated in sperm-egg membrane fusion (Primakoff et al, 1987). In addition to fertilin ␣ and fertilin ␤, the gene expression of several members of the ADAM family has been detected in somatic and spermatogenic cell components of prepubertal and adult rat testis and other organs (Frayne et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Currently it remains unknown what the fusogen is that mediates this process. Early experiments implicated a family of proteins known as the fertilins (Primakoff et al, 1987). The fertilins a and b are the founding members of the ADAM (A Disintegrin and Metalloprotease) family.…”
Section: Cell-cell Fusionmentioning
confidence: 99%